2010
DOI: 10.1111/j.1745-4557.2010.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Nutritional Value of Commercially Available Cocoyam and Potato Tubers in South Africa

Abstract: Potato (Solanum tuberosum) is a popular staple food in South Africa, whereas cocoyam (Colocasia esculenta) remains unpopular and not well known outside KwaZulu-Natal Province, where it is cultivated mainly for subsistence. A comparative study of the nutritional compositions of commercially available tubers of both crops in South Africa was carried out. The results showed that the tubers of the two crops were high in carbohydrate and energy but low in lipid contents. Although potato was significantly higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
37
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 24 publications
19
37
3
Order By: Relevance
“…The low moisture content for Treatment 1 on Magogoya variety and Treatment 3 on Ghana Variety is important as it enables long storage by minimizing fungal contamination and spoilage on cocoyam and also during transportation to the markets. The percentage ash content fall within the range reported in the literature, (Lewu et al, 2010) which is between 1 -5%. The ash content of Ghana variety was however lower than the other two local varieties.…”
Section: Discussionsupporting
confidence: 85%
“…The low moisture content for Treatment 1 on Magogoya variety and Treatment 3 on Ghana Variety is important as it enables long storage by minimizing fungal contamination and spoilage on cocoyam and also during transportation to the markets. The percentage ash content fall within the range reported in the literature, (Lewu et al, 2010) which is between 1 -5%. The ash content of Ghana variety was however lower than the other two local varieties.…”
Section: Discussionsupporting
confidence: 85%
“…This result is supported by a previous study [45] in that, boiling of cocoyam tubers increase the bioavailability of Fe.…”
Section: Mineral Profilesupporting
confidence: 90%
“…() and Lewu et al. (). The carbohydrate content showed that sample A had the highest value of 86.25 ± 0.17% followed by sample B (85.65 ± 0.12%).…”
Section: Resultsmentioning
confidence: 99%